2022
DOI: 10.3389/fbioe.2022.1022376
|View full text |Cite
|
Sign up to set email alerts
|

Correlational analysis of three-dimensional spinopelvic parameters with standing balance and gait characteristics in adolescent idiopathic scoliosis: A preliminary research on Lenke V

Abstract: Background: Adolescent idiopathic scoliosis (AIS), the most common spinal deformity, possibly develops due to imbalanced spinal loading following asymmetric development. Since altered loading patterns may affect standing balance and gait, we investigated whether a correlation exists between balance ability, gait pattern, and the three-dimensional radiographic spinopelvic parameters in AIS patients.Methods: A cross-sectional observational study was conducted with 34 AIS patients (aged 10–18 years) and an equal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Several studies investigated abnormalities in gait patterns due to AIS using motion capture systems and force platforms. Subjects with AIS showed significantly reduced stance [ 52 , 53 ] and increased swing phases [ 52 , 54 ] compared to controls. Abnormalities in ground reaction forces (GRF) during gait were also reported: Bruynell et al [ 55 , 56 ] found stronger anteroposterior and vertical as well as weaker mediolateral impulses of the ground reaction forces during gait initiation in subjects with AIS, while Sung et al [ 57 ] found a greater mediolateral peak force in the dominant limb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated abnormalities in gait patterns due to AIS using motion capture systems and force platforms. Subjects with AIS showed significantly reduced stance [ 52 , 53 ] and increased swing phases [ 52 , 54 ] compared to controls. Abnormalities in ground reaction forces (GRF) during gait were also reported: Bruynell et al [ 55 , 56 ] found stronger anteroposterior and vertical as well as weaker mediolateral impulses of the ground reaction forces during gait initiation in subjects with AIS, while Sung et al [ 57 ] found a greater mediolateral peak force in the dominant limb.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al [ 58 ] showed greater in-phase and lower anti-phase coordination between the thorax and the pelvis during gait. AIS did not seem to affect walking speed, stride length, and cadence of the subjects [ 21 , 52 , 60 ]. Subjects with AIS showed greater gait asymmetries [ 54 , 56 , 57 , 60 ], particularly in terms of GRF, step length, stance duration, and swing phases between the right and left feet.…”
Section: Resultsmentioning
confidence: 99%